Synergistic potential of α-Phellandrene combined with conventional antifungal agents and its mechanism against antibiotic resistant Candida albicans - Riya Bhattacharya; Prashant Sharma; Debajyoti Bose; Manish Singh (CABI Agriculture and Bioscience)
Abstract Candida albicans is resistant to various antifungal drugs, this presents a significant problem on a global scale. This study investigates a novel approach on the potential fungicidal effects of α-Phellandrene combinations with fluconazole and amphotericin B against antibiotic resistant C. albicans. The agar well diffusion experiment was used to measure the anti-candida activity of α-Phellandrene which exhibited a zone of inhibition of 24 ± 0.5 mm and 22 ± 0.5 mm against the C. albicans cells (MTCC277 and ATCC90028), respectively. Additionally, the fungicidal minimum inhibitory concentration (MIC) ranged 0.0312–0.0156 mg/ml (w/v) against C. albicans strains. It was determined to have powerful and efficient antifungal action against Candida cells. Further, the synergistic potential was evaluated by employing a time kill assay and a checkerboard technique, respectively, which revealed after 16 h, the colony count of C. albicans cells ATCC90028 (2.56 ± 0.33) and MTCC277 (2.53 ± 0.33) dropped by a log10 when treated with a combination of α-Phellandrene and Fluconazole and α-Phellandrene and amphotericin B exhibited synergy against both C. albicans strains ATCC90028 and MTCC277 (2.42 ± 0.28 and 2.00 ± 0.21) log10 reduction in colony count, respectively, Additionally, 16–624-fold increase in the antifungal efficacy of clinical medicines, with total cell death occurring after 16 h. α-Phellandrene and antifungal drugs were tested in combination with the osmoprotectant test, ergosterol test and FESEM observations to determine their modes of action. In the era of multidrug-resistant diseases antibiotic resistance can be curtailed in its tracks with the help of combination treatments that allow for lower drug doses.